2011
DOI: 10.1007/s10661-011-2295-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological assessment of French Atlantic lakes based on phytoplankton, phytobenthos and macrophytes

Abstract: Biological elements, including phytoplankton, phytobenthos, macrophytes, benthic invertebrates and fish, are employed by the EU Water Framework Directive (WFD) 2000/60/EC as ecological indicators for the assessment of surface waters. The use of primary producers (phytoplankton, phytobenthos and macrophytes) for water quality assessment has a long history, and several methods have been developed worldwide. In this study, we used these three communities to assess the ecological status of five natural lakes locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 56 publications
2
26
3
5
Order By: Relevance
“…Some authors have shown that diatom metrics developed for rivers are strongly correlated with pressure gradients in lakes (Blanco et al 2004, Bolla et al 2010, Cellamere et al 2012). This outcome leads to questions regarding the need for distinct lake-diatom assessment tools.…”
Section: Do Diatoms Respond Differently In Lakes and Rivers?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have shown that diatom metrics developed for rivers are strongly correlated with pressure gradients in lakes (Blanco et al 2004, Bolla et al 2010, Cellamere et al 2012). This outcome leads to questions regarding the need for distinct lake-diatom assessment tools.…”
Section: Do Diatoms Respond Differently In Lakes and Rivers?mentioning
confidence: 99%
“…Because UK lakes have fewer point-source discharges of organic matter and their littoral regions have longer residence times compared with rivers, taxa strongly associated with organic pollution (e.g., Nitzschia palea, Fistulifera saprophila) are less likely to thrive. Blanco et al (2004), Bolla et al (2010), and Cellamere et al (2012) all used metrics developed for rivers, but many of their sites were compressed into the upper half of the scale of the metrics. The river TDI used in our study fared better, perhaps because of its origin as an index of inorganic, rather than organic, enrichment (Kelly and Whitton 1995).…”
Section: Do Diatoms Respond Differently In Lakes and Rivers?mentioning
confidence: 99%
“…More effort has been done to improve the monitoring using benthic diatoms in rivers than in lakes (Cantonati and Lowe, 2014). However, from several years things changed and some authors applied existing river diatoms indices to the littoral zone of lakes (Blanco et al, 2004;Bolla et al, 2010;Cellamare et al, 2011) while others developed new tools based on diatoms communities (Schaumburg et al, 2007;Stenger-Kovács et al, 2007;Marchetto et al, 2013;Bennion et al, 2014) to respond to the demands of lakes assessment. Indeed, whereas phytoplankton is considered as the main ecological indicator on lakes, and usually is used to assess the overall lake quality, littoral diatoms demonstrated their efficiency to assess point source pollution and to be early warning of lake's deterioration (Cantonati and Lowe, 2014;Rimet et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because the phytoplankton functional groups approach can be used without geographic limitations (Padisák et al, 2009;Crossetti and Bicudo, 2008b;Becker et al, 2009;Pasztaleniec and Poniewozik, 2010), and habitat requirements and phytoplankton are sensitive to changes in water quality (Çelekli and Öztürk, 2014), it is a potential monitoring tool for the assessment of ecological status in the context of the Water Framework Directive (Cellamare et al, 2012). For instance, phytoplankton functional groups estimated reliable water quality states between hypertrophic and oligotrophic conditions in a reservoir of Turkey (Çelik and Sevindik, 2015), indicated eutrophication due to human impacts along the river Loire in France (Abonyi et al, 2012), and allowed an ecological assessment of French Atlantic lakes (Cellamare et al, 2012).…”
Section: Reaction Of Phytoplankton Functional Groups To Ecological Stmentioning
confidence: 99%
“…For instance, phytoplankton functional groups estimated reliable water quality states between hypertrophic and oligotrophic conditions in a reservoir of Turkey (Çelik and Sevindik, 2015), indicated eutrophication due to human impacts along the river Loire in France (Abonyi et al, 2012), and allowed an ecological assessment of French Atlantic lakes (Cellamare et al, 2012).…”
Section: Reaction Of Phytoplankton Functional Groups To Ecological Stmentioning
confidence: 99%